2008
DOI: 10.1063/1.3003881
|View full text |Cite
|
Sign up to set email alerts
|

ZnO/poly(9,9-dihexylfluorene) based inorganic/organic hybrid ultraviolet photodetector

Abstract: Solution processed inorganic/organic hybrid films of ZnO nanoparticles and poly(9,9-dihexylfluorene) (PFH) are sandwiched between two electrodes to form bulk heterojunction in this letter. The devices obtained show high ultraviolet photo-to-dark current ratio of about three orders of magnitude for −1V bias with a relatively fast response speed of less than 200ms after aging in air for enough time. The spectral response covers 300–420nm, with its peak locating around 335nm. Those results indicate that the ZnO/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Organic/inorganic hybrid devices, which combine the advantages of each component and overcome their disadvantages, usually show obvious superiority [11]. Hybrid UV detector with a high UV photo-to-dark current ratio and a fast response speed containing PFH and ZnO nanoparticles was reported [12] by our group.…”
Section: Introductionmentioning
confidence: 97%
“…Organic/inorganic hybrid devices, which combine the advantages of each component and overcome their disadvantages, usually show obvious superiority [11]. Hybrid UV detector with a high UV photo-to-dark current ratio and a fast response speed containing PFH and ZnO nanoparticles was reported [12] by our group.…”
Section: Introductionmentioning
confidence: 97%
“…It is reported that PFH/inorganic hybrids own good near-ultraviolet response because of the charge transfer between the components under UV irradiation [18,19]. However, defects in the inorganic electron acceptor like ZnO will delay the transient photoresponse of the device [19]. The organic alternative, naphthalene diimide (NTCDI) derivatives for example, could be a better choice in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (9,9-dihexylfluorene) (PFH) is a well-known p-type conjugated polymer with bandgap of about 3 eV, and the film of which can be readily obtained by spin-coating. It is reported that PFH/inorganic hybrids own good near-ultraviolet response because of the charge transfer between the components under UV irradiation [18,19]. However, defects in the inorganic electron acceptor like ZnO will delay the transient photoresponse of the device [19].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of organic/inorganic p-n junction, Schottky junction has been become a promising area because of their potential applications in various electronic devices such as photodiodes, field effect transistors and photodetectors [1]. ZnO is a direct wide band gap ( 3.3 eV) semiconducting material having large exciton binding energy ( 60 meV) at room temperature, making it prominent for short wavelength optoelectronic devices and transparent electronics.…”
Section: Introductionmentioning
confidence: 99%